Analisis Strategi Pemasaran dalam Upaya Peningkatan Daya Saing UMKM Kabupaten Bekasi - Gatot Sugiri (Journal of Economics and Management (JECMA), 2022)
Marketing strategy has an important role for MSMEs. The important role of the right marketing strategy will be able to increase the competitiveness of products produced by MSMEs, especially in Bekasi Regency. In an effort to develop a marketing strategy, complete information is needed regarding the market, consumers and the products needed. Lack of information that supports the determination of marketing strategies will of course make it difficult for MSMEs to compete. The purpose of this study is to analyze the application of marketing strategies in an effort to increase the competitiveness of MSMEs in Bekasi Regency. Method of analysis: using a descriptive approach with qualitative methods through the stages of data reduction, data presentation and drawing conclusions using SWOT analysis. The results of this study are, MSMEs in the Bekasi Regency area are members of the Bekasi Regency MSME Forum community.